Prescribing direct‐acting oral anticoagulants – Mind the evidence gap. Issue 11 (13th July 2022) - Adeyeye, Elizabeth; Maniero, Carmela; Magavern, Emma F.; Ferner, Robin E.; McGettigan, Patricia
Abstract : Direct‐acting oral anticoagulants (DOACs) are licensed for the prevention of thromboembolism in non‐valvular atrial fibrillation, amongst other indications. Prescribers use information derived from the summary of product characteristics which is based on the key trials supporting the DOAC's market authorisation. However, prescribers may not be aware of the limitations within these trials regarding underrepresentation of patient populations commonly encountered in clinical practice and how this may adversely impact them. This review highlights the gaps in the licensing evidence using four clinical vignettes that explore prescribing challenges in older adults, female patients, patients with obesity and patients from non‐Europid ethnic backgrounds.